Historiography, religion, and state in medieval India - Chandra, Satish (New Delhi : Har-Anand Publications, 1996)
Articles on Indian historiography and religion.
Keywords: Middle Ages -- Historiography; Historiography -- India; India -- History -- 1000-1765 -- Historiography; India -- Religion